Efektifitas Bimbingan Kelompok untuk Meningkatkan Kreativitas Peserta Didik: Meta Analysis - Irma Ari Irawan, Tb Moh; Rusmana, Nandang; Budiman, Nandang; Hananto, Ipung; Yudha, Eka Sakti (Universitas Muhammadiyah Metro, 2022)
Creativity is something to create new things, modify, and the ability to find solutions to challenging situations. Optimization efforts to develop students' creativity can be carried out with various strategies, including group guidance. On this basis, researchers are interested in conducting a meta-analysis study on the effectiveness of group guidance in increasing student creativity. This study aimed to determine the effect of group guidance in increasing students' creativity based on reviews of similar studies. The research method used is a method of meta-analysis. Researchers conducted a literature study with a research range from 2008 to 2020 obtained through Google Scholar, Garuda Portal, and student journals or research on the campus website. The keywords used to search for research samples include group guidance, creativity, creative thinking, and problem-solving. The search then resulted in the identification of 38 research study samples. Then the researchers conducted a comprehensive research study, ultimately finding 12 research samples that met the criteria and were eligible for a meta-analysis. Researchers conducted data analysis using the Jamovi application to calculate the effect size. The research results show that the influence of group guidance can increase students' creativity.